Undenatured Type II Collagen (UC-II) in Joint Health and Disease: A Review on the Current Knowledge of Companion Animals - Gencoglu, Hasan; Orhan, Cemal; Sahin, Emre; Şahin, Kazım (Mdpi, 2020)
Simple Summary Osteoarthritis (OA), the most common joint disease affecting humans and animals, is a painful, degenerative, and inflammatory disease that affects synovial joints and ultimately leads to loss of mobility. Non-pharmacological preventive approaches, several pharmaceutical therapeutic agents, and some medicines may reduce the progression of OA in animals. Many clinical and experimental studies have revealed that the undenatured form of type II collagen (UC-II) offers common health benefits to patients with OA. Abstract OA is quite common in companion animals, especially in large breed dogs and horses. Collagen, the most abundant protein of mammals, has specific connective tissue types for skin, bones, reticulate, basal lamina, bones, cell surfaces, while type II collagen (UC-II) forms the main structure of cartilage tissue. Even at the smaller dosages, UC-II has also been reported to be more effective than the glucosamine and chondroitin sulfate supplements, which are the supplements most frequently used in the market. In this review, we summarize the effects of UC-II on joint health and function in health and disease conditions in companion animals.
Keywords: collagen; inflammation; joint degeneration; osteoarthritis; pain